A delayed diagnosis of high-grade spondylolisthesis. Issue 3 (March 2022) - Kolenko, Ana Maria G.; Bauer, Jennifer M.
ABSTRACT: Spondylolysis, or pars defect, occurs in nearly half of children with back pain. Despite the marked prevalence, diagnosis of spondylolysis with spondylolisthesis often is delayed or missed secondary to referred pain and uncharacteristic presentation. This article describes an 8-year-old patient with 15 months of right heel pain who was initially treated by her primary care provider for presumed Sever disease before being referred to orthopedics. After orthopedic consultation, she was diagnosed with a high-grade spondylolisthesis with L5 nerve root compression. Although spondylolysis is an infrequent diagnosis, particularly in a patient this young, missing the diagnosis can significantly reduce a patient's quality of life.